THE PRODUCTION OF KNOWLEDGE IN THE FIELD OF PHYSICAL EDUCATION: A REFLEXION FROM AN EPISTEMOLOGICAL STANDPOINT (Fiep Bulletin - online, 2015)
The goal of this paper is to make a brief historical review about the main areas of interest in the field of physical education (PE) and discuss some aspects of the epistemological debate that has been permeating this field. In the sixties, there was a considerable preoccupation with some  pedagogical aspects of the corporeal practices, mainly health and moral education.  In the seventies, the physical education field became almost exclusively interested in physical fitness and sports.  In the eighties, it started to demonstrate a  preoccupation with ideological issues and with a need to help building a more just and equal society.  In the nineties, this field started also to be concerned with epistemological issues. While some authors have been defending that the field of physical education should restrict itself to pedagogical issues, based on the complexity theory and in some authors of the field of PE that work with this theory, I present some arguments in favor that this field should be maintained multidisciplinary, since it is exactly in this characteristic that resides its potential to significantly contribute to education, health, leisure and quality of human life.
Keywords: Physical education; epistemology; history.